2021
DOI: 10.2147/ijn.s315040
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Honey-Derived Exosomes Containing Antimicrobial Peptides Against Oral Streptococci

Abstract: Purpose: Recently, our group found exosome-like extracellular vesicles (EVs) in Apis mellifera honey displaying strong antibacterial effects; however, the underlying mechanism is still not understood. Thus, the aim of this investigation was to characterize the molecular and nanomechanical properties of A. mellifera honey-derived EVs in order to elucidate the mechanisms behind their antibacterial effect, as well as to determine differential antibiofilm properties against relevant oral streptococci. Methods: A. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…A recent study revealed that insect peptides exert antibiofilm effects against major nosocomial pathogens via non-specific mechanisms (37). extracellular vehicles (EVs) from honeybees have exhibited antibiofilm effects against S. mutans and Streptococcus sanguinis (38). Human antimicrobial peptide LL-37 has substantial antibacterial effects (39).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that insect peptides exert antibiofilm effects against major nosocomial pathogens via non-specific mechanisms (37). extracellular vehicles (EVs) from honeybees have exhibited antibiofilm effects against S. mutans and Streptococcus sanguinis (38). Human antimicrobial peptide LL-37 has substantial antibacterial effects (39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the peptides Defensin-1 and Jellein-3 were quantified with direct ELISA, as previously described (23). Briefly, one microgram of RJEV protein and negative controls (pre-bleed serum 1:1000, human mesenchymal stem cell protein 30 μg) as well as respective standards were incubated overnight.…”
Section: Methodsmentioning
confidence: 99%
“…No reuse allowed without permission. Furthermore, the peptides Defensin-1 and Jellein-3 were quantified with direct ELISA, as previously described (23).…”
Section: Exosomal Markers and Cargomentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from H 2 O 2 and MGO, the recently explored exosome-like extracellular vesicles in honey [ 54 ] display a pronounced antibacterial effect against S. mutans, mediated through nanomechanical alterations resulting in membrane damage [ 55 ]. Detailed molecular characterisation of these honey-derived vesicles has further revealed that MRJP-1, defensin-1 and jellein-3 are cargo proteins in vesicles.…”
Section: Honey—its Composition and Antibacterial/antibiofilm Propertiesmentioning
confidence: 99%